Search for narrow high-mass resonances in proton-proton collisions at root s=8 TeV decaying to a Z and a Higgs boson - (:unkn) unknown (ELSEVIER, 2015)
A search for a narrow, high-mass resonance decaying into Z and Higgs ( H) bosons is presented. The final state studied consists of a merged jet pair and a tau pair resulting from the decays of Z and H bosons, respectively. The analysis is based on a data sample of proton-proton collisions at a center-of mass energy of 8 TeV, collected with the CMS experiment in 2012, and corresponding to an integrated luminosity of 19.7 fb(-1). In the resonance mass range of interest, which extends from 0.8 to 2.5 TeV, the Z and H bosons are produced with large momenta, which implies that the final products of the two quarks or the two tau leptons must be detected within a small angular interval. From a combination of all possible decay modes of the tau leptons, production cross sections in a range between 0.9 and 27.8 fb are excluded at 95% confidence level, depending on the resonance mass. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Resonance production; Jets; Tau leptons; Boosted topology; HIERARCHY